EFEKTIVITAS MODEL PEMBELAJARAN SCIENCE TECHNOLOGY SOCIETY (STS) DISERTAI DENGAN MIND MAP (MM) UNTUK MEMBERDAYAKAN KETERAMPILAN PROSES SAINS SISWA - Listiani, Ivayuni (Premiere Educandum, 2015)
The purpose of this study was to determine the effectiveness of a Science TechnologyÂ Society model accompanied with Mind Map to empower the ability to science proccesÂ skills. This study was a quasi-experimental study. The study used a one-group pretestposttestdesign.TheÂ populationofthestudywasallstudentsofgradeXofPublicSeniorHighSchool 7 Surakarta in the academic year of 2013/2014. Sample was take nusingcluster random sampling technique with a sample of 27 students. The instrument usedwas questionnaire, observation sheets, interviews, and tests. The ability to KPS data wastested with the Paired sample t-test and calculated by N-gain. The results showed theeffectiveness of STS models accompanied with MM, in whichit had been successful inincreasing the ability to KPS with a value of N-gain of 0.54 and the result was significanceat p = 0.000, making the ability be long to âmediumâ category. Based on the results ofresearch and hypothesis testing, it can be concluded that STS model accompanied withMM was effective in empowering the ability to KPS of the tenth graders of Senior HighSchool 7 Surakarta in the academic year of 2013/2014.Keywords: Science Technology Society (STS), Mind Map (MM), ScienceProccesSkills